How Much Depressed are Lung Tuberculosis Patients in Tangerang, Banten Province, Indonesia? - Darmawan, Tirta; Pardamean, engelberta; Anabella, Vinsensa; Mark, Mark; Widjaja, Amelia Gianina (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction : Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis (MTB) and mostly attacks the lung and other organs. In patients with pulmonary tuberculosis, depression can occur and the factors that can cause it are age, sex, marital status, level of education, emplyment, long suffering from pulmonary tuberculosis and comorbidities. The purpose of this study is to show the prevalence and also degree of depression in patients with lung Tuberculosis in Tangerang, Banten Province, Indonesia.Methods : The study design is cross sectional by asking participants to fill Zung Self-Rating Depression Scale that have been translated to Indonesian language. Participants were 129 patients with lung tuberculosis in Siloam General Hospitals Lippo Karawaci, Puskesmas Kutai and Puskesmas Curug.Results : Mean age of the 137 patients with lung tuberculosis is 47.73 + 8.50 years old, and the mean of their height and weight are 163.94+ 7.59 centimeters and 51.10 + 7.40 kilograms. More than a half of the patients are male (69%), almost a half of the patients are low educated (48%) and almost all of the patients have been married (93.8%). More than a half of the lung tuberculosis patients experience deppression (70,5%). Approximately a half of the lung tuberculosis patients are having mild depression (50.4%). There is 1 patient is having severe depression (0.8%).Conclusion : Degree of depression in adult patients suffer from lung Tuberculosis in Tangerang, Banten Province, Indonesia is high. More than a half of adult lung Tuberculosis patients are having depression. Depression is one of problems that should be concerned and also treated in patients with lung tuberculosis. Psychiatrist involvement in managing patients with lung tuberculosis is needed.